MODEL-MODEL PERMAINAN KARTU DALAM PEMBELAJARAN MAHĀRAH AL QIRĀAH - Arifin, Ahmad (STIQ Amuntai, 2021)
Reading is a communication process between the reader (al Qāri) and the writer (al Kātib) to understand the reading text and get the messages contained in it through words/written language that has a cognitive relationship (thinking) between spoken language and written language. However, learning al Qirāah taught in schools is very difficult to learn, tedious, and uninteresting. It can even make students feel afraid to read it. This research uses qualitative descriptive research, and the goal is to describe the models of card games in learning mahārah al Qirāah at State High School 5 Banjarmasin. Learning al Qirāah taught in schools is very difficult to learn, tedious and uninteresting, and can even make students feel afraid to read it. However, the results show that card game models are very motivating and increase the enthusiasm and passion of learning for students, make it easier for students to understand the material, and help the boring learning process become fun and exciting. Gaming models using the card in mahārah al Qirāah that can be used are the word card model, sentence card model, question and answer card model, answer complementary card model and pictorial mufradat card model. Keywords: Card Model, Learning, Mahārah Al Qirāah